150 Jahre „Kapital“ – und kein Ende: Unsystematische Anmerkungen zu einer unendlichen Geschichte - Heinrich, Michael (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2017)
This article discusses the conditions of a paradoxical reception of Marx’s ‘Capital’, which rests on a distorted classification of Marx’s critique of classical political economy as a last representative of this school. This article reveals some examples of an implicit critique in Marx’s arguments and discusses the question of what was really new in Marx’s theory of value and capital. Furthermore, the article presents some stereotypical examples of contemporary critiques of Marx and in conclusion sketches the unfinished state of ‘Capital’ and what we can expect from forthcoming publications in MEGA.